Tactile perception of the roughness of the end of a tool: what role does tool handle roughness play? - Zampini, M; Mawhinney, S; Spence, C (2006)
We investigated whether the perceived roughness of the end of a tool is influenced by the texture of the handle used to hold it. Participants rated the roughness of the ends (caps) of a series of tools by rubbing them along their forearm, and indicated the perceived roughness of the tool's cap by means of an anchored visual scale. The caps of the tools had one of eight different levels of roughness varying from very smooth (sample 1) to very rough (sample 8). The participants held the tool handle in one hand while rubbing the cap of the tool against their contralateral forearm. The tool handle was either smooth (similar in smoothness to sample 1) or else very rough (matched in roughness to sample 8). Overall, participants were remarkably good at ignoring the roughness of the tool's handle when discriminating the roughness of the tool's cap. Nevertheless, the roughness of the tool handle was shown to modulate roughness judgments concerning the tool cap under certain conditions: in particular, tool caps at the rougher end of the scale (6 and 7) were rated as being significantly less rough when the participants held tools with a rough handle than when they held tools with a smooth handle. Our results therefore demonstrate a small but significant effect of the roughness of the handle of a tool on the perceived roughness of its cap.